Routledge Handbook of Descriptive Rhetorical Studies and World Languages (Taylor & Francis, 2023)
topoi; endoxa; political discourse; adversariness; polyphony; speech; debate; government; Greece; troika
English
Keywords: thema EDItEUR::C Language and Linguistics::CJ Language teaching and learning; thema EDItEUR::J Society and Social Sciences::JP Politics and government::JPH Political structure and processes; topoi; endoxa; political discourse; adversariness; polyphony; speech; debate; government; Greece; troika